História, impactos e rupturas: o uso comercial nas edificações da Região central de Cruz Alta (1970-2020) - Villani, Monique (2020)
This dissertation runs through a specific part of the Pinheiro Machado Street, in Cruz Alta, Rio Grande do Sul. Which is a set of four streets located between the General Firmino de Paula and Érico Veríssimo squares, a space with social and historical importance to the city, mainly because it was one of the first streets to form its urban network. Throughout the years, it has undergone considerable changes in its spatial arrangement, especially due to the commercial development which has caused some architectural interventions in the historical buildings located in this area. The objective of this study is to reinforce the dialogue and to evaluate the conflicts resulted from the relationship among space, architecture, interventions, identity and memory. Some historical, political and urbanistic characters are present because they clarify the composition of this setting and of its urban landscape, approaching therefore, a visual plastic posture. The problematics is the way how the external architectural interventions, the social media and the advertising are applied over these buildings as well as the effects of intensive commercialization at this area. As a result, these elements tend to stand out and the historical buildings become unknown which also affects the urban memory. This research approaches Cruz Alta’s history, its morphological development, its places and identity elements as well as some of the main architectural styles present in the downtown buildings and around them. It also evaluates how the space is dominated by real estate speculation and high commercialization.In the theorical foundation there are authors like Rossi (1998) and Jacobs (2000), addressing the use of urban areas and also the changes that have been occurred in the cities in regard to the space and the memory. Carlos (2007), portrays the city as a space to be explored, a place which aims the financial capital, the trade and the economy, when they become dominant factors. Cavalari (2011), brings the history of Cruz Alta and some of its identity elements as the foundation of its historical background. Some academic journals, articles and term papers were used to complete the research sources. In relation to the study field, technical researches, descriptions and observations were made. The space is a mixture of historical, social, cultural, economic, and architectural elements – which contributes to its unique identity. Its transformation throughout the years as well as its resilience to the actions that were imposed are factors that must be highlighted. Even though some essential characteristics have been changed, its huge identity representation to the city remains the same, and it is one of the reasons of its recognition as social role.